Development of the Basket Challenge Game Using Scratch Application - Sipahutar, Mery Nova Marito Br; Sembiring, Rafika Sari Br (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2024)
The Basketball Challenge game was created using Scratch, a visual programming platform that enables the development of educational games in an easy and interactive manner. Basketball Challenge is designed with a storyline where players must collect as many balls as possible to reach the required score to advance to the next level. If players fail to collect the balls according to the target, the game will end with a game over, and players will have to start again from the initial level. Conversely, if players manage to collect the balls to meet the target, they will proceed to the next level. This study aims to explore the development process of this game, including level design, gameplay mechanics, asset creation, as well as testing and debugging. The results indicate that Scratch is an effective tool for developing educational games that can be played by all age groups, providing an enjoyable gaming experience while also training players' cognitive and motor skills.